2012
DOI: 10.1073/pnas.1200425109
|View full text |Cite
|
Sign up to set email alerts
|

Tandem mass spectrometry identifies many mouse brain O -GlcNAcylated proteins including EGF domain-specific O -GlcNAc transferase targets

Abstract: O -linked N -acetylglucosamine ( O -GlcNAc) is a reversible posttranslational modification of Ser and Thr residues on cytosolic and nuclear proteins of higher eukaryotes catalyzed by O -GlcNAc transferase (OGT). O -GlcNAc has recently been found on Notch1 extracellular domain catalyzed by EGF domain-specific OGT. Aberrant O -GlcNAc modification of brain proteins has been linked to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
269
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 272 publications
(280 citation statements)
references
References 55 publications
9
269
2
Order By: Relevance
“…We believe that this constitutes the first broad proteomic analysis of O-GlcNAc-modified proteins in primary human T cells. Many of the proteins that we identified appeared in prior proteomics studies (55,(76)(77)(78), supporting the validity of our results. However, we also identified novel O-GlcNAc substrates, including ARNT, HCLS1, ZAP-70, SHIP1, LCK, and PI3K.…”
Section: Discussionsupporting
confidence: 87%
“…We believe that this constitutes the first broad proteomic analysis of O-GlcNAc-modified proteins in primary human T cells. Many of the proteins that we identified appeared in prior proteomics studies (55,(76)(77)(78), supporting the validity of our results. However, we also identified novel O-GlcNAc substrates, including ARNT, HCLS1, ZAP-70, SHIP1, LCK, and PI3K.…”
Section: Discussionsupporting
confidence: 87%
“…S3). Whereas previous studies have detected O-GlcNAc on EGF20 of Notch using mass spectral methods and other techniques (36,37,41,42), here we confirm the presence of a HexNAc on EGF20 and several other EGF repeats. Although we cannot differentiate GlcNAc from GalNAc using these methods, the localization of the HexNAc to peptides containing O-GlcNAcylation sites suggests a GlcNAc modification.…”
Section: Drosophila Notch Shows Glycosylation Consistent With the Presupporting
confidence: 73%
“…The current putative consensus sequence for O-GlcNAc exists on a serine or threonine between the fifth and sixth conserved cysteine (C 5 XXGX(T/S)GXXC 6 ) (41). Of note, whereas Matsuura et al and others have reported the presence of O-GlcNAc on Notch (36,37,41,42), like the other types of O-glycosylation, no data regarding how efficiently the sites on Notch are modified have been provided.…”
mentioning
confidence: 99%
“…However, the recent development of lectin weak affinity chromatography (LWAC) and chemical/enzymatic tagging strategies has facilitated enrichment of these modified peptides from complex proteolytic digest mixtures (9,10), and the advent of electron transfer dissociation (ETD) mass spectrometry has facilitated the robust assignment of modification sites (11). These advances have been used effectively for studies in mammalian systems, and over 1,000 O-GlcNAc-modified proteins have been identified (9)(10)(11)(12)(13)(14). However, no similar study has been reported in plants, and thus it's unclear whether O-GlcNAc modification controls similar cellular process in plants and animals.…”
mentioning
confidence: 99%